Association Between TERT rs2736098 Polymorphisms and Cancer Risk-A Meta-Analysis - Zhou, Mi; Jiang, Bo; Xiong, Mao; Zhu, Xin (Frontiers in Physiology, 2018)
Background: Cancer remains a leading cause of death and constitutes an enormous burden on society worldwide. The association between the human telomerase reverse transcriptase (TERT) gene variant rs2736098 polymorphisms and cancer predisposition remain inconclusive. Objective and methods: Databases including Pubmed and Embase were systematically searched from inception to September 15,2017 to retrieve studies investigating the association between the TERT variant rs2736098 polymorphisms and cancer risk in accordance with previously determined exclusion and inclusion criteria. The pooled odds ratios (ORs) and corresponding 95% confidence intervals (CIs) were evaluated using random or fixed effects models. Results: Thirty-one case-control studies from 29 articles with 15837 cases and 19263 controls were screened out after a systematic search. Pooled analysis demonstrated that the TERT variant rs2736098 G > A polymorphism was significantly correlated with cancer risk in all populations (A versus G: OR = 1.134, 95% CI = 1.051–1.224, P = 0.001; AA vs. GG: OR = 1.280, 95% CI = 1.087–1.508, P = 0.003; GA versus GG: OR = 1.125, 95% CI = 1.020–1.240, P = 0.018; GA/AA versus GG: OR = 1.159, 95% CI = 1.047–1.283, P = 0.004). In the subgroup analysis based on cancer type, the TERT rs2736098 with the A allele was 1.299 times more frequent than that with the G allele (OR = 1.299, 95% CI = 1.216–1.386) under the allelic genetic model in lung cancer, and 1.152 times (OR = 1.152, 95% CI = 1.032–1.286) that in bladder cancer. Conclusions: This meta-analysis demonstrated significant correlations between the TERT variant rs2736098 polymorphisms and cancer susceptibility. The A allele in the rs2736098 G > A polymorphism contributes to susceptibility in many types of cancer, especially lung cancer and bladder cancer.